Ropivacaine with intraspinal administration alleviates preeclampsia-induced kidney injury via glycocalyx /alpha 7 nicotinic acetylcholine receptor pathway. Issue 5 (2nd May 2022) - Sun, Shen; Lu, Yaojun; Tian, Fubo; Huang, Shaoqiang
ABSTRACT: Preeclampsia is characterized by hypertension and proteinuria, which is associated with kidney injury. Glycocalyx (GCX) degradation mediated endothelial injury can result in proteinuria and kidney damage. alpha 7 nicotinic acetylcholine receptor (α7nAChR) connects nervous and immune systems to respond to stress or injury. We aimed to explore the protective effect and mechanism of intraspinal analgesia on maternal kidney injury in preeclampsia. Endotoxin-induced preeclampsia rats treated with ropivacaine via intraspinal administration. Renal histopathological examination was performed, cell apoptosis in the kidney, the levels of Glycocalyx markers of Syndecan-1 and heparin sulfate (HS) in maternal serum, Syndecan-1 along with α7nAChR in the kidney were measured. Our results showed that kidney injury was obviously in preeclampsia rats with proteinuria, endothelial damage, higher apoptosis rate, increasing levels of Syndecan-1 and HS in serum, upregulated Syndecan-1 expression but downregulated α7nAChR expression in kidney. Preeclampsia rats treated with intraspinal injected ropivacaine attenuated preeclampsia-induced kidney injury as Syndecan-1 and HS were decreased in serum, Syndecan-1 expression was suppressed as well as α7nAChR was activated in the kidney. Our results suggested that Ropivacaine administered through the spinal canal may protect preeclampsia-induced renal injury by decreasing GCX and α7nAChR activation. Graphical Abstract: uf0001